2019
DOI: 10.1007/s40093-019-00306-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of active and passive aeration on composting of household biodegradable wastes: a decentralized approach

Abstract: Purpose Present work aims at studying the influence of active (using external aerator) and passive (natural) aeration on composting of household biodegradable wastes. Methods To study the suitability of these reactors to household conditions, continuous loading was carried out for a period of 60 days. Both the reactors were loaded with cooked as well as raw vegetable and fruit waste. Physico-chemical parameters such as temperature, pH, C/N ratio, moisture content, total organic content, Total Kjeldahl Nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Moreover, decentralized approach can be implemented for select types of wastes at reduced investment and operating cost. Finally, the approach is easily adaptable to the existing waste management practices (Bhave and Kulkarni, 2019). Integration of different approaches for solid waste management optimizes the existing systems and implements new waste management systems.…”
Section: Waste Collection and Recyclingmentioning
confidence: 99%
“…Moreover, decentralized approach can be implemented for select types of wastes at reduced investment and operating cost. Finally, the approach is easily adaptable to the existing waste management practices (Bhave and Kulkarni, 2019). Integration of different approaches for solid waste management optimizes the existing systems and implements new waste management systems.…”
Section: Waste Collection and Recyclingmentioning
confidence: 99%
“…it has the potential as a place of livelihood such as a scavenger. A waste needed special attention which was prioritized by immediate action from the authorities, as it had been identified as one of the three main sources of environmental degradation in Asian countries by the World Bank (19). Solid waste management that was decentralized in a system area and formed as an effort to provide a livable and hygienic environment (20).…”
Section: Discussionmentioning
confidence: 99%
“…Composting is an aerobic, microorganism-mediated fermentation process, performed particularly for the solid fraction, used to transform organic materials into more stable compounds. The product obtained following processing is the compost, a highly valuable product for agriculture use, since it can improve a soil's physical, chemical, and microbiological qualities [13,14]. A more efficient technique for processing organic waste in order to obtain qualitative compost is the thermophilic composting in enclosed systems, using specially designed bioreactors.…”
Section: Issues Of Traditional Waste Management Systems For Fruit And...mentioning
confidence: 99%
“…A study that assessed the effects produced by active and passive aeration on composting household biodegradable wastes, in a decentralized approach [13], found that active aeration is the most effective approach for residential organic waste treatment especially for reducing the unpleasant odors and obtaining financial savings by reducing processing time. Other research studies have approached the effect produced by the intermittent rotation with natural aeration for enclosed bioreactors [38][39][40], or the combined continuous aeration accompanied by rotary mixing process for reducing the active period [15] for mixtures of fruits, vegetables, and chicken manure.…”
Section: Main Findings and Concerns Related To Composting Processesmentioning
confidence: 99%